Fabric Heat Transfer by Conduction and Radiation (Journal of Fiber Bioengineering and Informatics, 2023)
Persons exposed to solar heat radiation in hot and dry climates are at increased risk of heat illnesses. Clothing can reduce such exposure. The effectiveness of clothing to reduce such heat loading depends on the ability of the fabric to reflect this heat radiation. However, incomplete reflection results in fabric heating which will heat the body by conduction. The protection against heat radiation by a garment can be offset by the retention of metabolic heat due to insulation. This will counteract the IR attenuation benefits offered by the clothing. An accurate understanding of such a trade-off is needed in order to optimize the selection of clothing when managing heat stress resulting from exposure to solar IR heat radiation. Laboratory experiments were performed on multiple layers of Cotton, Nylon, Wool and Polyester fabric to evaluate their heat insulation characteristics and IR heat attenuation properties. The relationship between fabric layers and IR attenuation properties was examined under controlled laboratory conditions. The results of this study showed that fabric insulation heat gain and corresponding IR radiation attenuation was proportional to the number of fabric layers used. However, the IR heat radiation attenuation was significantly greater with each additional fabric layer than the heat gain penalty associated with fabric insulation. Additionally, heat transfer by condition was seen to contribute about 18% of the radiant heat transfer to the body. Separating the fabric from the body using a spacer will reduce this amount of heat transfer to the skin. The results of this study show that multiple fabric layers can significantly reduce the risk of IR heat radiation overexposure while limiting the metabolic heat build-up inside protective clothing. The study also confirms that by selecting the appropriate number of fabric layers, it is possible to optimize the IR heat radiation protection while limiting metabolic heat build-up inside clothing.
Keywords: Solar Heat Stress; IR Heat Radiation Attenuation; Multi-layered Clothing; Fabric Insulation; Heat Transfer by Conduction.